Barriers to adopting therapeutic virtual reality: the perspective of clinical psychologists and psychotherapists - Felnhofer, Anna; Pfannerstill, Franziska; Gänsler, Lisa; Kothgassner, Oswald D.; Humer, Elke; Büttner, Johanna; Probst, Thomas (Frontiers in Psychiatry, 2025)
Background and objectiveDespite evidence supporting the effectiveness of Virtual Reality (VR) for mental disorders, VR adoption in therapy remains low. As VR-technology continues to advance, it is crucial to examine individual and contextual barriers preventing implementation of therapeutic VR.MethodsAn online survey with closed and open-ended questions regarding knowledge of VR, VR-usage and barriers to VR adoption was conducted among clinical psychologists and psychotherapists in Austria (Mage=51.71 years, 76% women).ResultsOf 694 participants, only 10 reported using therapeutic VR. Chi-square tests revealed significant differences regarding interest in therapeutic VR based on prior experience, employment status, professional training, and therapeutic cluster. Besides a small age effect, no effects of gender or professional experience were found. Participants interested in VR (interest group, IG) frequently cited barriers and other reasons (see thematic analysis) for not having used VR yet. Those not interested in VR (no interest group, NIG) indicated a lack of relevance, no perceived advantage, or disinterest as reasons for not using VR. Thematic analysis identified four themes shared by both IG and NIG, each encompassing group-specific sub-themes: professional barriers (lack of knowledge, training, time, personal reasons), financial barriers (costs, cost-benefit-ratio), therapeutic barriers (clinical applicability, concerns about “real” therapeutic relationship), and technological barriers (immature technology, cybersickness, no equipment).ConclusionsSignificant barriers to the adoption of therapeutic VR among clinical psychologists and psychotherapists are gaps in knowledge and training, financial constraints, and lack of motivation, all of which highlight the need for training and financial support to enhance VR implementation.